Purse seining in India - a review - Pravin, P.; Meenakumari, B. (Indian Journal of Fisheries, 2016)
Purse seining is one of the most efficient and advanced commercial fishing methods of recent times, used for harvesting shoaling fishes. Purse seines are surrounding nets in which the bottom of the net is closed after encircling the fish school, by a pursing line which prevents fish from escaping downwards by diving. In India, purse seining was introduced in the south-west coast in the late 1950s to harvest shoaling fishes like anchovies, sardines and mackerels. With the success of purse seining in the country, there were rapid technological changes in the purse seine fishing method and substantial increase in the number and size of both fishing craft and gear. This present review provides an insight into the developmental changes in purse seine fishing in India and highlights future strategies.